Human Resources Accounting And its Reflection on Quality Cost (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The development of human resources training programs can assist in agreat deal in creating products of high quality with quantitive advantage for the economicunit;through the sale of products by prices higher of the peer products price in the arket,or decreasing production costs which lead into increusing the unet  profits. for these reasons, the human resources have got great importance for their great role in  any economy,and they havestarled to consentrate on accounting these resource.From this point of view, this research has handied human resources accounting and their effect on quality costs.  In(MID-Refinery Company),quality costs are determined ,then we have larified the reality of training and development in the ompany .finally ,we have come into the conclussions and recommend  dations ,the most important conclussions are ,most economic Units lask enough knowledge about the concept of quality costs ,their elements, and heuce the roli of human sources accounting in getting berefit of trained human resources in performance with higher efficiency , quality and speed  ,The most important recommendations are the necessity of supporting studies and researches dealing with human  resources ccounting  and quality costs : and preparing the suitable teaching programs about varions  Specializations ,pursuiting their accomplishing and evaluating to invest  heir own costs.